ISOLASI DAN IDENTIFIKASI SENYAWA PENANGKAP RADIKAL 2,2-DIFENIL-1-PIKRILHIDRAZIL DALAM DAUN KELOR (Moringa oleifera, Lamk.) - , BETA RIA ERIKA MARITA DELLIMA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Free radical is suspected as mediator of various degenerative diseases. Antioxidant can scavenge the free radical and detoxify it. One of the potential plant developed as natural antioxidant is kelor (Moringa oleifera, Lamk). The aims of this research were to evaluate the activity of radical scavenging of 2,2- diphenyl-1-picrylhydrazyl (DPPH), the contents of phenolic total and flavonoid total of kelor leaves extract and its fractions and to isolate the active component responsible for DPPH radical scavenging activity. Dry powder of kelor leaves was macerated using ethanol 80%. Macerate was concentrated using rotary evaporator and called as ethanol extract of kelor leaves. The extract was partitioned using n-hexane, ethyl acetate, and water. The result of the partition was then concentrated in order to get n-hexane, ethyl acetate and water extracts. All kelor leaves extract was determined for its activity of radical scavenging of DPPH, the contents of total phenolic and total flavonoid by spectrophotometry. The most active extract (ethyl acetate extract) was subsequently fractionated using vacuum liquid chromatography with stationary phase of Merck gel silica 1.07734.1000 sized 0.063-0.200 and the mobile phase consisted of n-hexane, chloroform, ethyl acetate, and methanol in various composition. The fractionation of ethyl acetate extract of kelor leaves yielded 12 fractions. Fraction number 12, as the most active fraction of free radical scavenger, was then hydrolyzed and continued with isolation process using column chromatography with stationary phase of Merck gel silica 1.09385.1000 sized 0.040-0.063 with the mobile phase consisted of chloroform, ethyl acetate, and methanol in various composition. Yellow isolate on effluent 35-38 was tested for its purity and identified using UV spectrophotometry, high performance liquid chromatography (HPLC) photodiode array detector, infrared (IR) spectrophotometry, and mass spectrometry. The most active fraction (fraction no. 12) had IC50 value of 15.02 Î¼g/mL, while the contents of total phenolic and total flavonoid were 11.14 % wt/wt gallic acid equivalent and 44.01 % wt/wt rutin equivalent. Identification using UV, IR and mass spectrometry showed that the isolate in effluent 35-38 contained quercetin aglycone.